Bacterial infection in compensated viral cirrhosis impairs 5-year survival (ANRS CO12 CirVir prospective cohort). Issue 2 (28th October 2015) - Nahon, Pierre; Lescat, Mathilde; Layese, Richard; Bourcier, Valérie; Talmat, Nabila; Allam, Setty; Marcellin, Patrick; Guyader, Dominique; Pol, Stanislas; Larrey, Dominique; De Lédinghen, Victor; Ouzan, Denis; et al.
Abstract : Objective: To assess incidence and prognostic significance of bacterial infections (BIs) occurring in compensated viral cirrhosis. Design: This prospective study involved 35 French centres. Inclusion criteria were biopsy-proven HCV or HBV cirrhosis, Child–Pugh A and no previous hepatic complications. Cumulative incidence (CumI) of events was estimated in a competing risks framework. Results: 1672 patients were enrolled (HCV 1323, HBV 318, HCV-HBV 31). During a median follow-up of 43 months, 234 BIs occurred in 171 patients (5 year CumI: 12.9%), among whom 14.6% had septic shock. Main localisations included the urinary tract (27.4%), lung (25.2%) and peritoneum (10.7%) (other, 86 (36.7%)). Most BIs occurred as a first event prior to liver decompensation (n=140, 81.8%) and were community-acquired (CA, 84.2%). The risk of BI was higher in patients with HCV than in patients with HBV (5 year CumI: 15.2% vs 5.5%, p=0.0008). Digestive localisation, concomitant interferon-based treatment, isolation of resistant bacteria and non-CA BIs were associated with lowest probability of resolution. The occurrence of a first BI impaired survival in patients infected with HCV (5 year survival: 60.2% vs 90.4%, p<0.001) and patients infected with HBV (5 year survival: 69.2% vs 97.6%, p<0.001). BIs represented the third cause of death (14.1%) after liver failure and liver cancer. BI risk factors comprised older age, lower albumin, proton pump inhibitor intake and absence of virological eradication/control. Conclusion: BI mostly occurs as a first complication and represents a turning point in the course of compensated viral cirrhosis. Its occurrence impacts long-term prognosis and may define a subgroup of patients in whom adaptation of management is warranted.